Pre-treatment endocrine–nutritional signatures predict clinical benefit from PD-1/PD-L1 blockade in hematologic malignancies - Huang, Ningjing; Guan, Yu (Frontiers in Nutrition, 2026)
Hematologic malignancies pose significant global health burdens, with programmed cell death protein-1 (PD-1)/programmed cell death ligand 1 (PD-L1) inhibitors revolutionizing treatment in subtypes like classical Hodgkin lymphoma (cHL) and primary mediastinal large B-cell lymphoma (PMBCL), achieving high objective response rates (ORR). However, efficacy varies widely, with limited success in multiple myeloma (< 10% ORR) and leukemias, underscoring the need for better predictors beyond tumor-intrinsic biomarkers. This review highlights pre-treatment endocrine–nutritional signatures as key host factors influencing immunotherapy outcomes. Dysregulated hormones (cortisol, thyroid, sex steroids, insulin/insulin-like growth factor-1, adipokines) and nutritional status (vitamin D, zinc, protein-energy malnutrition, iron metabolism) modulate T-cell exhaustion, myeloid suppression, and tumor microenvironment dynamics, often leading to resistance. Evidence from cohorts shows hypercortisolism, hypothyroidism, insulin resistance, vitamin D deficiency, and hypoalbuminemia correlate with inferior ORR, progression-free survival, and overall survival, while thyroid immune-related adverse events and moderate obesity predict benefit. In hematologic contexts, marrow infiltration exacerbates these imbalances, explaining heterogeneous responses. Integrated signatures (e.g., Glasgow Prognostic Score, Prognostic Nutritional Index) offer superior prognostic value, enabling targeted interventions like vitamin D supplementation, metformin, or nutritional support to enhance immune checkpoint inhibitor efficacy. Mechanistic insights reveal convergence on mTOR/IFN-γ pathways and microbiome modulation. Translating these to clinical panels could personalize immunotherapy, addressing gaps in hematologic malignancies literature and improving outcomes in relapsed/refractory settings.